Roam scale: K3 tools for engineers / Rohana Hassan and Amira Ruzailin Dzulkifli - Hassan, Rohana; Dzulkifli, Amira Ruzailin (2022)
ROAM Scale is a bearing stress scale that acts as an alternative to determine the value of modification factor, K3 while K₃ is a modification factor for bearing stress in order to get permissible stresses for timber flexural members.